Efeito do sildenafil na genotoxicidade induzida pelo estresse oxidativo em camundongos ateroscleróticos - Rodrigues, Bianca de Paula e (2013)
It is well known that enhanced production of reactive oxygen species (ROS) leads to oxidative stress observed in atherosclerosis and that ROS can also cause damage in cellular macromolecules, including DNA. Considering previous report that sildenafil, an inhibitor of phosphodiesterase 5 (PDE5), have antioxidant effects, in the present study we evaluated the effect of this drug on genotoxicity of blood mononuclear cells (MNC) and liver cells from atherosclerotic apolipoprotein E knockout mice (apoE-/- ). To accelerate and aggravate the spontaneous hyperlipidemia and atherosclerosis in apoE−/− mice, 8-week-old animals were fed a Western-type diet. Animals were randomly distributed into three different groups: (a) apoE−/− mice administered with the PDE5 inhibitor sildenafil (apoE−/− sildenafil, Viagra® , 40 mg/kg/day, for 3 weeks, by oral gavage, n=18), (b) apoE-/- mice administered with vehicle (apoE-/- vehicle, n=14) and (c) Wild-type C57Black/6 mice (WT, n=16). Then, animals (18-week-old) were euthanized and MNC isolated by density gradient and liver cells extracted by enzymatic action. Oxidative stress was determined by superoxide anion (•O2 - ) production using DHE probe. 106 cells were diluted with 1mL PBS and incubated with 160 μM DHE for 30 min at 37ºC in the dark, then washed and resuspended in 0.5ml of PBS-iFBS. A FACSCanto II cytometer was used for the flow cytometric analysis. Measurements were performed in triplicate and 10,000 events were used for each measurement. The genotoxicity analysis was performed using the alkaline comet assay that consists to obtain from individual cells, an array with a fluorescent halo in the format of a comet corresponding to the quantity of the fragmented DNA. The DNA helices ruptures extensions were evaluated by the image intensification method, where 100 cells were randomly selected (50 in each slide) using the analysis program CASP. The measurements of the comets were obtained by the parameters of the tail moment and percentage tail DNA. In addition, comets with more than 25% DNA in the tail (damage level moderate-high) were quantified between groups. Data are expressed as mean±SEM. Statistical analysis were performed by one-way ANOVA followed by Bonferroni post hoc test (p<0.05). Flow cytometric analysis showed a significant increase (78%) in superoxide anion (•O2 - ) production in apoE-/- vehicle mice MNC compared to WT and treatment with sildenafil decreases the levels of •O2 - in animals apoE-/- . In the DNA damage analysis all parameters used (%tail DNA, tail moment and number of comets with damage level moderate-high) showed an increase in the DNA fragmentation in both MNC and liver cells of animals apoE-/- vehicle when compared to WT control, and sildenafiladministered apoE-/- mice exhibited minimal DNA damage in those cells similar to WT mice. Our data shows that atherosclerosis increases ROS production leading to oxidative stress. Apparently, increased ROS interact with the DNA leading to fragmentation and, interestingly, the treatment with sildenafil was able to reduce ROS production inhibiting DNA damage. The novelty of this study is that sildenafil may offer a new perspective to the use of PDE5 inhibitors to protect against DNA damage, in cells involved in the inflammatory and dyslipidemic processes that accompany atherosclerosis.